2023
DOI: 10.1186/s40795-023-00683-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with wasting and stunting among children aged 06–59 months in South Ari District, Southern Ethiopia: a community-based cross-sectional study

Abstract: Background Child undernutrition is a major public health problem in Ethiopia despite different nutrition-specific and sensitive interventions implemented by the government. However, evidence regarding the burden and responsible factors is limited in the South Ari district. Hence, this study aimed to assess factors associated with wasting and stunting among children aged 06–59 months in the South Ari district, Southern Ethiopia, 2021. Methods A comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
3
1
0
Order By: Relevance
“…Children with ages of 6-12 months and 12-23 months are at a higher risk of stunting than children with ages of 0-6 months. This finding is in line with that of other studies (Toma et al, 2023;Mulyani et al, 2022). A cohort study of children's growth and development in Bogor also found that the Z-score for height according to children's age tended to decrease as the children aged.…”
Section: Resultssupporting
confidence: 92%
“…Children with ages of 6-12 months and 12-23 months are at a higher risk of stunting than children with ages of 0-6 months. This finding is in line with that of other studies (Toma et al, 2023;Mulyani et al, 2022). A cohort study of children's growth and development in Bogor also found that the Z-score for height according to children's age tended to decrease as the children aged.…”
Section: Resultssupporting
confidence: 92%
“…This study revealed a statistically significant association between the wealth index (WI) and wasting among school-age children, which aligns with previous findings in the Philippines [52], and South Ari District in Southern Ethiopia [53]. Furthermore, the odds of wasting were significantly lower for children aged 11-14 years compared to those aged 6-10 years, which is consistent with studies conducted in Gondar town, northwestern Ethiopia [32], Gedeo Zone in South Ethiopia [48], Northern Sri Lanka [51], the Philippines [52], and North East of Morocco [54].…”
Section: Discussionsupporting
confidence: 90%
“…Child with good dietary diversity status was 45% less likely to be stunted that their counter parts. This is supported by a study conducted Gedeo zone, East and West Gojjam and South Ari district in Ethiopia (50)(51)(52). Beyond Ethiopia, the nding was in line with different studies in Yogyakarta, Tanzania, Indonesia and Bangladesh (38, 53-55).…”
Section: Discussionsupporting
confidence: 85%